Oxygen variability and tropical Atlantic circulation - Cruise No. M119 - September 8 - October 12, 2015 - Mindelo (Cape Verde) - Recife (Brazil) ... - Brandt, Peter (DFG-Senatskommission für Ozeanographie, 2016)
R/V METEOR cruise M119 was a joint effort of the Kiel Collaborative Research Centre SFB 754 ("Climate - Biogeochemistry Interactions in the Tropical Ocean") involving the BMBF joint project RACE and the German-French-African Cooperative Project AWA. The first part of the cruise focused on the oxygen minimum zone (OMZ) of the Eastern Tropical North Atlantic (ETNA). The main goal was the quantification of ventilation processes including lateral and vertical mixing and oxygen advection (SFB SP A3 and A4). Other foci of this cruise were the role of zooplankton and particles for oxygen consumption and biogeochemical cycles (SFB SP B8), the study of epi- and mesopelagic communities of macrozooplankton and micronekton (a project of the Cluster of Excellence "Future Ocean"), and the quantification of N2 fixation. All hydrographic and current data were acquired as planned (with some reduction of the number of CTD stations along 23°W), including the successful recovery of all moorings. At the equator, the cruise ... : METEOR-Berichte ...